(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
The revision of holotypes and paratypes of Lithophyllum contii Mastrorilli, 1967 and Lithophyllum giammarinoi Mastrorilli, 1 968, coming from the Rupelian calcarenitic limestone of the "Molare Formation" (Tertiary Piedmont Basin), demonstrates that there are not enough elements to permit the distinction of two different species. So, according to priority, Lp. giammarinoi must be consider junior synonym of Lp. contii, that is here redescribed as Lithophyllum contii Mastrorilli sensu amplo.